Psychological Manipulation in Psychological Thrillers: A Case Study of “The Housemaid” by Freida McFadden - Siti Alifia Ananda Ardiani; Otong Setiawan Djauhari (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Psychological thrillers as a genre have become a powerful vehicle for exploring the dynamics of power, trauma, and manipulation in human relationships. This article discusses psychological manipulation in the psychological thriller genre, focusing on Freida McFadden's novel The Housemaid. The main issue raised is how manipulation is constructed and displayed through the psychological behavior of the characters. The purpose of this study is to uncover the narrative techniques and psychological strategies used by the author in building tension and directing the reader's perception. This study uses a qualitative method with a psychological literary approach, analyzing the behavior of the main characters, namely Andrew Winchester, Millie, and Nina in their interactions to identify elements of manipulation. The results show that McFadden effectively uses unreliable narratives, character isolation, and changing power dynamics to enhance psychological tension. The conclusion shows that these elements work together to create an intense and disturbing reading experience, and reveal the important role of manipulation in the psychological thriller genre.